Role of HMGB1 and its associated signaling pathways in human malignancies - Sourour Idoudi (14153457) (2023)
The High-Mobility Group Box-1 (HMGB1), a non-histone chromatin-associated protein, plays a crucial role in cancer growth and response to therapy as it retains a pivotal role in promoting both cell death and survival. HMGB1 has been reported to regulate several signaling pathways engaged in inflammation, genome stability, immune function, cell proliferation, cell autophagy, metabolism, and apoptosis. However, the association between HMGB1 and cancer is complex and its mechanism in tumorigenesis needs to be further elucidated. This review aims to understand the role of HMGB1 in human malignancies and discuss the signaling pathways linked to this process to provide a comprehensive understanding on the association of HMGB1 with carcinogenesis. Further, we will review the role of HMGB1 as a target/biomarker for cancer therapy, the therapeutic strategies used to target this protein, and its potential role in preventing or treating cancers. In light of the recent growing evidence linking HMGB1 to cancer progression, we think that it may be suggested as a novel and emergent therapeutic target for cancer therapy. Hence, HMGB1 warrants paramount investigation to comprehensively map its role in tumorigenesis. Other Information Published in: Cellular Signalling License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cellsig.2023.110904 Additional institutions affiliated with: Education and Research - HMC, Qatar University Health - QU